“Indians on White Lines”: Bureaucracy, Race, and Power on Northern British Columbian Traplines, 1925–1950 - Vogt, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
After British Columbia imposed universal mandatory trapline registration in 1925, game wardens, Department of Indian Affairs officials, and Indigenous people in the provincial north quickly came into conflict over the place of Indigenous trappers, Indigenous claims to trapping territory, and the applicability of colonial game regulations to Indigenous communities. Although some scholars have suggested that the primary result was the large-scale dispossession of Indigenous communities, roughly half of the province’s registered traplines remained officially in “Indian” hands, raising questions about how bureaucrats recognized, classified, and sought to administer such lines. In practice, game law enforcement was often uncertain, arbitrary, and frequently governed by informal arrangements that existed alongside the official regulations. By the 1930s, trappers with Indian status had gained some measure of protection and exemption from the game laws, in part due to an energetic campaign by the federal Indian Department. To bureaucrats, however, the never-completed quest to define and solidify a racialized boundary between “Indian” and “white” trappers, trapping, and traplines often became as important as — or even more important than — the ostensible provincial goal of game conservation and the federal goal of Indigenous economic prosperity.